(untitled) - O'Neil, Patrick (San Francisco, California, 1994)
The book offers a solid introduction to the concepts of logical database design, physical layout, commands, utilities, security, and recovery, showing how each is critical to price-performance. It points out the differences between theory and practice, advantages and disadvantages of industry standards, and important differentces among SQL dialects of commercial database systems
Keywords: Database management